Ricardian inference: Charles S. Peirce, economics, and scientific method - Kevin D. Hoover; James R. Wible (Duke University, Center for the History of Political Economy (CHOPE), 2017)
Standard histories of economics usually treat the "marginal revolution" of the midnineteenth century as both supplanting the "classical" economics of Smith and Ricardo and as advancing the idea of economics as a mathematical science. The marginalists - especially Jevons and Walras - viewed Cournot's (1838) book on mathematical economics as a seminal work on which they could build. Surprisingly, the scientist, philosopher, and logician Charles S. Peirce discovered Cournot before the marginalist economists and possessed a deeper appreciation of his mathematical approach. While Peirce's contributions to economics are limited, the influence of economics on his philosophy is subtle and not well understood. In a number of fragments, Peirce, who, despite Ricardo's lack of mathematical form, nonetheless regarded him as a paradigmatic mathematical economist, refers to "Ricardian inference," as a fundamental contribution to scientific method. Two, perhaps complementary, options are explored as to exactly what Peirce meant by Ricardian inference. On the one hand, he associates Ricardo with the "primipostnumeral syllogism," which is a sort of generalization to uncountably infinite sets of what Peirce calls Fermatian inference (often referred to as mathematical induction). On the other hand, he holds up Ricardo as an exemplar of the "analytical method," which is Peirce's name for a hybrid form connecting analogy, abduction, and induction. On either account, economics plays a larger and more fundamental role in Peirce's philosophy of science than is generally understood.
Keywords: B4; B41; B10; B16; B31; 330; Charles S. Peirce; David Ricardo; Antoine Augustin Cournot; Ricardian inference; analogy; abduction; induction; economics; transfinite cardinals